Forming the ecological network for ukrainian carpathians on principles of carpathians convention strategy - Беспалько, Руслан; Солодкий, В.Д.; Казімір, Іван (Ecology and noospherology, 2013)
For the preservation purpose of valuable and typical components of landscape and biological variety the role of the forests and natural protected territories of the Bukovina Carpathians and Precarpathians in formation of an ecological network of the Carpathian region on the basis of the Carpathian Convention principles is investigated. The Carpathian Convention plays an outstanding role as the multilateral agreement between Poland, Romania, the Czech Republic, Slovakia, Serbia, Hungary and Ukraine concerning concentration of joint efforts for preservation, renewal and balanced usage Carpathian region natural resources and also for inconsistencies overcoming of the social, economic and ecological normative and target principles of natural resources management. Cause-and-effect relations of the forests and reserved territories development as compound structural elements of an econetwork of the region and observance of the principles of a sustainable development are established, in particular: − multi-purpose forest exploitation with increase of ecologization of production; − woodiness increasing of the territory; − biological variety preservation of forest ecosystems; − steadiness increasing of forest ecosystems to negative environment factors; The scheme of the structurally functional organization of the harmonization program for an econetwork of the region has been developed. It has been proved that for implementation of harmonization system of structural and component elements of an econetwork it is necessary to develop at the state level the National Program of an ecological safety of the Carpathian region, where to consider implementation of a complex of nature protection actions. It will give the chance to work productively for realization of the of the Carpathian Convention principles, in particular: − to improve an ecological situation in the region by adhering control of requirements of the environmental protection legislation by stakeholders; − to provide the balanced development of productive forces of the region taking into account ecological components, intersector harmonization of the action plans, achievement of the integrated regulation of development of mountain and foothill areas;
ФОРМУВАННЯ ЕКОМЕРЕЖІ УКРАЇНСЬКИХ КАРПАТ НА ПРИНЦИПАХ СТРАТЕГІЇ КАРПАТСЬКОЇ КОНВЕНЦІЇ
Keywords: ecological network; Bukovina Carpathians; Carpathian Сonvention; preservation of biodiversity; ecologization of environmental management; balanced development of region